"The Bane of a Music Librarian's Existence": Why and How Music Libraries Preserve Scores with Spiral and Comb Bindings. (3rd July 2021) - Shirts, Peter
ABSTRACT: While popular with music publishers, spiral and comb bindings for music scores are problematic for music libraries for many reasons, especially long-term preservation. While recommendations exist for how libraries should treat these scores, only a few outdated research studies detail actual binding practices. This article summarizes and analyzes findings from a 2018 survey of 50 libraries of various sizes and budgets in the United States and Canada, describing common ways libraries deal with spiral- and comb-bound scores, the main perceived problems with these types of bindings, and the diversity of decision workflows.